Plant products for the management of yellow mosaic disease of mungbean and urdbean (The Journal of Plant Protection Sciences, 2020)
An experiment was designed to test the efficacy of a few botanical extracts on the yellow mosaic of mug bean. Maximum reduction in disease incidence recorded were 66.70 and 63.65 percent in mungbean and Urdbean, respectively by eight sprays of Clerodendrum aculeatum. Whereas, eight sprays of Boerhaavia diffusa root extract could reduce the disease incidence by 60.27 and 58.20 per cent followed by Azadirachta indica leaf extract by 42.43 and 42.92 percent in mungbean and urdbean, respectively. Maximum plant height (70.90 and 56.20 cm), primary branches (6.36 and 6.38 per plant), secondary branches (13.56 and 10.68 per plant), nodules (27.48 and 37.69 per plant), pods (17.25 and 22.85 per plant), seed yield (4.43 and 3.89 g per plant) were recorded in eight sprays with Clerodendrum aculeatum leaf extract followed by eight sprays with Boerhaavia diffusa root extract and Azadirachta indica leaf extract.
Keywords: Mungbean; urdbean; management; botanicals; yellow mosaic virus